ANALISIS DETERMINAN KEJADIAN ANEMIA REMAJA PUTRI SEKOLAH MENENGAH ATAS WILAYAH KERJA PUSKESMAS SENTUL KABUPATEN BOGOR - Dika Maretika Sobari; Tria Astika Endah Permatasari; Dewi Purnamawati (IAKMI South Tangerang Branch, 2023)
ABSTRACT Background: Anemia is a condition of red blood cells or commonly called hemoglobin is below normal. World Health Organization (WHO) is in the range of 40-80% and as many as 57% of them are suffered by adolescent girls. Southeast Asia is the region with the highest prevalence of anemia at 42%. The incidence of anemia in women of childbearing age in Indonesia in 2019 reached 30.6% and the prevalence of anemia in adolescent girls was 32%, the majority of adolescents who experienced anemia were in the age range of 10 - 18 years. In West Java the incidence of anemia reached 41.5%.. Objective: The purpose of this study was to analyze the factors associated with the incidence of anemia among adolescent girls of private high schools in the sentul puskesmas working area, Bogor district. Method: Quantitative research with Cross Sectional design. 125 samples. The sampling technique used Purposive Sampling. research using the sample formula with hypothesis testing 2 population proportions. Result: 45.6% of adolescent girls were anemic, 50 (56.8%) of adolescent girls were not compliant with taking Fe anemia tablets, 36 (59.0%) rarely consumed iron-source food intake, 30 (48.8%) rarely consumed iron-blocking food/drink intake, 38 (51.4%) were undernourished, 44 (46.3%) of adolescent girls had good knowledge of anemia, 10 (52.6%) had a history of infection, 29 (43.9%) had normal menstrual cycles, 45 (47.4%) had normal menstrual duration, 3 (60.0%) had abnormal menarche and anemia. There is a relationship between adherence to taking Fe tablets, dietary intake of iron sources and nutritional status. Conclusion: The dominant factor causing anemia in adolescent girls is adherence to taking Fe tablets p=0.000; OR (95% CI) =5.869 (2.217 - 15.535). Keywords: Anemia, adolescent girls, Fe tablets. ABSTRAK Latar belakang: Anemia remaja putri menyebabkan perkembangan fisik dan psikis yang terganggu, penurunan kerja fisik dan daya pendapatan, penurunan daya tahan terhadap kelelahan, peningkatan angka kesakitan dan kematian. Tujuan: Untuk menganalisis determinan kejadian anemia remaja putri Sekolah Menengah Atas (SMA) swasta di wilayah kerja Puskesmas Sentul Kabupaten Bogor. Metode: Penelitian dengan desain Cross Sectional, dilakukan pada 125 remaja putri di tiga SMA swasta wilayah kerja Puskesmas Sentul, Bogor pada Bulan Januari-Maret 2023. Sampel dihitung dengan rumus uji hipotesis 2 proporsi populasi dengan teknik Purposive Sampling. Anemia diukur dengan pemeriksaan hemoglobin menggunakan alat easy touch GCHB. Analisis data menggunakan uji regresi logistik berganda dengan SPSS Versi 20. Hasil: Dari 125 remaja putri terdapat hampir separuh (45,6%) remaja putri mengalami anemia, 56,8% remaja putri tidak patuh mengkonsumsi tablet Fe. Faktor dominan yang berhubungan secara bermakna terhadap kejadian anemia adalah kepatuhan minum tablet Fe (P-value =0.000; OR=5.63 (2,23-14,21)). Faktor lainnya yaitu asupan makanan sumber zat besi (P-value=0,003; OR=2,94 (1,42-6,11)) Sedangkan faktor lainnya tidak berhubungan dengan anemia (P-value >0,05) Kesimpulan: Remaja putri yang tidak patuh mengkonsumsi tablet Fe lebih berisiko 5,63 untuk mengalami anemia dibandingkan remaja putri yang patuh mengkonsumsi tablet Fe. Untuk meningkatkan kepatuhan konsumsi tablet Fe pada remaja putri diperlukan sosialisasi kembali aplikasi “Ceria” yang digunakan dalam pemantauan kepatuhan konsumsi tablet Fe. Kata kunci: anemia, remaja putri, kepatuhan konsumsi tablet Fe, status gizi